Inflation with GDP, Unemployment and Remittances: An Outline of the Joint Effect on Nepalese Economy - Yadav Mani Upadhyaya,; Khom Raj Kharel, (Interdisciplinary Journal of Management and Social Sciences, 2022)
The major objective of this research is to examine the trend of inflation, the trend of Nepal's economic development, trends of unemployment, and trends of remittances. Likewise, another one is the analysis and the effect of inflation on the GDP, unemployment, and the remittances of Nepal. The method of this research is to analyze and use the secondary data to create a simple regression model based on econometrics. Furthermore, the article concludes the mathematical relation between inflation and economic growth, inflation and unemployment, and inflation and remittances. There is a positive strong relationship between inflation among GDP remittances and unemployment.